Long term Cardiovascular Manifestations of COVID - 19 - Ahmed, Khurshed; Sah, Sudhir Prasad; Khaled, Md Fakhrul Islam; Anwar, AFM Azim; Hoque, Md Harisul (University Heart Journal, 2022)
Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is well known for causing an acute respiratory disease, a number of patients after they get recovered from acute infection, subsequently experience a constellation of symptoms and events that lasts for more than 3 months. Adequate clinical data are now accumulating on the subacute and long-term effects of Covid-19 and can involve multiple organ systems. This spectrum of symptoms and late manifestations are thought to have a possible link with the covid-19 and this condition is named LONG COVID or POST-COVID. Some of the patients may show the ongoing evidence of cardiovascular damage on long term without having symptoms which may be picked up by different imaging modalities like CMR. There has been an increase in the number of COVID-19 patients in an exponential fashion so as to cause a collapse in the healthcare system in many countries across the world, with an effect not only on public health, but also on social and economic activities. University Heart Journal 2022; 18(2): 118-124